Unravelling the Aftermath: An Analysis of Post-Revocation of Semi-Autonomous Status of Indian Held Jammu and Kashmir - Nayeem Maqbool Hurrah; Niyamatullah; Kamran Naseem (ASIAN Journal of International Peace & Security (AJIPS), 2023)
India consistently impeded the semi-autonomous status of Jammu and Kashmir (J&K) and weakened the provisions of Article 370 several times through a series of more than fifty presidential orders spanning well over a half-century. However, to ensure the complete annexation of disputed territory, the Government of India unilaterally abrogated the semiautonomous status of Jammu and Kashmir and divided the state into two union territories - Jammu & Kashmir and Ladakh on 5th August 2019. This robbed the Muslim-majority state of its identity and thrown it into a state of paralysis. Since June 19, 2018, Jammu and Kashmir has been functioning without an elected government. The Lieutenant Governor (LG) led administration of Jammu and Kashmir is actively changing the demography of Jammu and Kashmir by providing voting and property rights to the non-locals, who were temporarily working in Jammu and Kashmir. This qualitative study employed historical and descriptive method, mostly relying on the secondary data to highlight India’s unconstitutional and undemocratic measures in Jammu and Kashmir after the revocation of semi-autonomous status. The study also analyzes the strategy of ’excessive militarism’ that Indian armed forces have adopted to muzzle and crush the pro-resolution movement of the Kashmiri people.